Reliability Assessment of Existing Equations Predicting the Shear Strength of Reinforced Concrete Beams without Stirrups - Arslan, Guray; Ibis, Aydogan; Alacali, Sema Noyan (TURKISH CHAMBER CIVIL ENGINEERS, 2014)
Codes keep the probability of shear failure low in order to prevent a reinforced concrete member from reaching its ultimate strength through shear failure, which is sudden and brittle. Numerous equations for predicting the cracking shear strength of a reinforced concrete beam without stirrups have been proposed in the previous studies. In this study, performance functions related to the equations given by four codes and seven researches are developed considering beams with various geometrical and material properties. The reliability of these equations is assessed based on the performance functions by using second-moment approach. According to the failure probabilities based on different distributions, it is observed that the equation given by EN92 is the most reliable one.
Keywords: Reinforced concrete; beam; shear strength; probabilistic; reliability; failure; Engineering